Foamable methyl methacrylate resin particles

CN119654371APending Publication Date: 2025-03-18KANEKA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380057226.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-02
Filing Date
2023-11-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing foamable acrylic resin particles have shortcomings in adhesion and welding properties, especially the opposite relationship between welding properties and adhesion properties, which makes it difficult to optimize simultaneously.

Method used

By applying magnesium stearate to the surface of foamable methyl methacrylate resin particles, resin particles having excellent weldability and adhesion inhibition are prepared in combination with a copolymerization step, a foaming agent impregnation step and a coating step.

Benefits of technology

It has achieved the suppression of adhesion of foamed particles and the improvement of the weldability of the foamed molded body, meeting the demand for simultaneously optimizing adhesion and welding properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259630720000281
    Figure BDA0005259630720000281
  • Figure BDA0005259630720000291
    Figure BDA0005259630720000291
Patent Text Reader

Abstract

Provided are foamable methyl methacrylate resin particles satisfying the following (i) and (ii): (i) it is possible to provide foam particles in which adhesion is suppressed, and (ii) it is possible to provide a foam molded article having excellent weldability. Foamable methyl methacrylate resin particles containing a base resin containing a methyl methacrylate unit and an acrylate unit as constituent units and a foaming agent are used, the foamable methyl methacrylate resin particles containing a specific amount of magnesium stearate on the surface thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to expandable methyl methacrylate resin particles. Background Art

[0002] In metal casting, lost foam casting (full mold casting) is known, in which a mold made of a foamed molded body is buried in casting sand, molten metal is poured into the foamed molded body to replace the foamed molded body with the metal, thereby casting a casting.

[0003] Conventionally, foamed molded articles obtained using expandable methyl methacrylate resin particles have been widely used as lost pattern for casting. By using such foamed molded articles as lost pattern for casting, a casting having a beautiful surface can be obtained.

[0004] For example, Patent Documents 1 to 3 disclose expandable acrylic resin particles containing an acrylic resin and a foaming agent.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-147736

[0008] Patent Document 2: Japanese Patent Application Publication No. 2021-24885

[0009] Patent Document 3: Japanese Patent Application Publication No. 2001-270959 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] However, the above-mentioned prior art still has room for improvement from the viewpoint of the adhesion of acrylic foamed particles obtained from the expandable acrylic resin particles and the weldability of the acrylic foam molded article.

[0012] One embodiment of the present invention provides expandable methyl methacrylate resin particles that satisfy the following (i) and (ii): (i) can provide expandable particles with suppressed blocking, and (ii) can provide an expandable molded article having excellent weldability.

[0013] Solutions for solving problems

[0014] The inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention.

[0015] That is, the expandable methyl methacrylate resin particles according to one embodiment of the present invention include: a base resin containing methyl methacrylate units and acrylate units as structural units; and a foaming agent.

[0016] The surface of the expandable methyl methacrylate resin particle contains 0.03 parts by weight or more and 0.14 parts by weight or less of magnesium stearate based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

[0017] In addition, a method for producing expandable methyl methacrylate resin particles according to one embodiment of the present invention includes:

[0018] A copolymerization step of copolymerizing a monomer mixture comprising methyl methacrylate monomers and acrylate monomers;

[0019] a blowing agent impregnation step of impregnating the obtained copolymer with a blowing agent; and

[0020] In the coating step, 0.03 parts by weight or more and 0.14 parts by weight or less of magnesium stearate is coated on the surface of the obtained expandable methyl methacrylate resin particle body based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

[0021] Effects of the Invention

[0022] One embodiment of the present invention has the effect of providing expandable methyl methacrylate resin particles that satisfy the following (i) expandable particles with suppressed blocking and (ii) expandable molded article having excellent weldability. DETAILED DESCRIPTION

[0023] An embodiment of the present invention is described below, but the present invention is not limited thereto. The present invention is not limited to the various configurations described below, and various changes can be made within the scope indicated in the claims. In addition, embodiments or embodiments obtained by combining the technical means respectively disclosed in different embodiments or examples are also included in the technical scope of the present invention. Furthermore, by combining the technical means respectively disclosed in each embodiment, new technical features can be formed. It should be noted that all the academic literature and patent literature recorded in this specification are cited as references in this specification. In addition, in this specification, unless otherwise specified, "A to B" indicating a numerical range means "above A (including A and greater than A) and below B (including B and less than B)".

[0024] In this specification, a structural unit derived from X monomer contained in a polymer or a copolymer may be referred to as "X unit".

[0025] In this specification, “expandable methyl methacrylate resin particles” may be referred to as “expandable resin particles”, “methyl methacrylate resin foamed particles” may be referred to as “foamed particles”, and “methyl methacrylate resin foamed molded article” may be referred to as “foamed molded article”.

[0026] [1. Technical idea of ​​one embodiment of the present invention]

[0027] Acrylic foamed beads obtained using the foamable acrylic resin particles disclosed in Patent Documents 1 to 3 have room for improvement from the viewpoint of achieving both (i) prevention of blocking of foamed beads and (ii) good weldability of foamed molded articles obtained from the foamed resin particles.

[0028] Conventionally, in order to prevent the sticking of expanded beads obtained from expandable resin particles, there is known a technique of adding a fatty acid metal salt to the surface of expandable resin particles.

[0029] Here, it is generally known that the more the adhesion of the foamed beads obtained from the foamable resin beads is suppressed, the worse the weldability of the obtained foamed molded article. That is, it is known that the adhesion of the foamed beads obtained from the foamable resin beads and the weldability of the obtained foamed molded article have an inverse relationship.

[0030] Therefore, the present inventors have studied suitable fatty acid metal salts from the viewpoint of weldability. In other words, the present inventors have studied fatty acid metal salts that do not deteriorate weldability.

[0031] As a result, the present inventors have obtained a surprising new finding that magnesium stearate not only does not deteriorate the weldability but can improve the weldability and can also significantly suppress blocking, thereby completing the present invention.

[0032] In particular, the finding that magnesium stearate can improve the weldability of a foamed molded article is a very surprising new finding that could not be anticipated from the prior art.

[0033] [2. Foamable methyl methacrylate resin particles]

[0034] The expandable methyl methacrylate resin particles according to one embodiment of the present invention include: a base resin containing a methyl methacrylate unit and an acrylate unit as structural units and a foaming agent, wherein the surface of the expandable methyl methacrylate resin particles contains 0.03 parts by weight or more and 0.14 parts by weight or less of magnesium stearate based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

[0035] Hereinafter, “expandable methyl methacrylate resin particles according to one embodiment of the present invention” may also be referred to as “present expandable resin particles”.

[0036] In this specification, expandable resin particles not containing magnesium stearate on the surface are referred to as "expandable resin particle bodies", and expandable resin particles containing magnesium stearate on the surface are referred to as "expandable resin particles".

[0037] The present expandable resin particles are expanded by a known method to provide expandable particles. The expandable resin particles are expanded by in-mold molding to provide a foamed molded article.

[0038] Since the foamable resin particles have the above-mentioned structure, they have the advantages of being able to provide foamable methyl methacrylate resin particles that satisfy the following (i) and (ii): (i) foamable particles with suppressed adhesion can be provided, and (ii) foamed molded articles with excellent weldability can be provided. The evaluation method of the adhesion of the foamable particles and the weldability of the foamed molded articles will be described in detail in the following examples.

[0039] (2-1. Base material resin)

[0040] The base resin contained in the present expandable resin particles contains a methyl methacrylate unit and an acrylate unit as structural units.

[0041] In addition, in this specification, the expression of "monomer" is sometimes omitted. Therefore, in this specification, for example, when simply expressing "methyl methacrylate" and "acrylate", they refer to "methyl methacrylate monomer" and "acrylate monomer", respectively.

[0042] In the base resin contained in the present expandable resin particles, relative to 100 parts by weight of the total amount of methyl methacrylate units and acrylate units, (a) preferably the content of the methyl methacrylate units is 93.0 parts by weight to 99.0 parts by weight, and the content of the butyl acrylate units is 1.0 parts by weight to 7.0 parts by weight, (b) preferably the content of the methyl methacrylate units is 94.0 parts by weight to 99.0 parts by weight, and the content of the acrylate units is 1.0 parts by weight to 6.0 parts by weight, (c) preferably the content of the methyl methacrylate units is 95.0 parts by weight to 99.0 parts by weight, and the content of the acrylate units is 1.0 parts by weight to 5.0 parts by weight, (d) preferably the content of the methyl methacrylate units is 95.5 parts by weight to 99.0 parts by weight, and the content of the acrylate units is 95.5 parts by weight to 99.0 parts by weight. (e) more preferably, the content of methyl methacrylate units is 96.0 parts by weight to 98.5 parts by weight, and the content of acrylate units is 1.5 parts by weight to 4.0 parts by weight, (f) more preferably, the content of methyl methacrylate units is 96.5 parts by weight to 98.0 parts by weight, and the content of acrylate units is 2.0 parts by weight to 3.5 parts by weight, (g) further preferably, the content of methyl methacrylate units is 97.0 parts by weight to 97.5 parts by weight, and the content of acrylate units is 2.5 parts by weight to 3.0 parts by weight, (h) particularly preferably, the content of methyl methacrylate units is 97.5 parts by weight, and the content of acrylate units is 2.5 parts by weight. When the content of methyl methacrylate units and the content of acrylate units in the base resin of the foamable resin particles are respectively within the above ranges, the foamable resin particles have the following advantages: (i) foamable particles with suppressed blocking can be provided and (ii) foamed molded products with excellent weldability can be provided.

[0043] In the base resin, when the content of the acrylate unit is within the above range relative to 100 parts by weight of the total amount of the methyl methacrylate unit and the acrylate unit, the foamable resin particles have the advantages of excellent foamability and being able to provide foamable particles with suppressed adhesion. In addition, the foamable resin particles (foamable particles) have the advantage of being able to provide a foamed molded article with excellent weldability.

[0044] In one embodiment of the present invention, the total content of methyl methacrylate units and acrylate units in 100 wt % of the base resin is preferably 95.0 wt % or more, more preferably 96.0 wt % or more, more preferably 96.5 wt % or more, more preferably 97.0 wt % or more, more preferably 97.5 wt % or more, more preferably 98.0 wt % or more, more preferably 98.5 wt % or more, more preferably 99.0 wt % or more, further preferably 99.5 wt % or more, and particularly preferably 100.0 wt % (in other words, the base resin consists of methyl methacrylate units and acrylate units). According to this configuration, the expandable resin particles have the following advantages: (i) it is possible to provide expandable particles with suppressed adhesion and (ii) it is possible to provide a foamed molded article with excellent weldability.

[0045] Examples of the acrylic acid ester unit include a methyl acrylate unit, an ethyl acrylate unit, a propyl acrylate unit, a butyl acrylate unit, a pentyl acrylate unit, a hexyl acrylate unit, and a 2-ethylhexyl acrylate unit.

[0046] The acrylate unit is preferably (a) one or more selected from the group consisting of methyl acrylate unit, ethyl acrylate unit, propyl acrylate unit, butyl acrylate unit, pentyl acrylate unit, hexyl acrylate unit and 2-ethylhexyl acrylate unit, more preferably (b) one or more selected from the group consisting of methyl acrylate unit, ethyl acrylate unit, propyl acrylate unit, butyl acrylate unit, pentyl acrylate unit and hexyl acrylate unit, further preferably (c) one or more selected from the group consisting of methyl acrylate unit, ethyl acrylate unit, propyl acrylate unit and butyl acrylate unit, and particularly preferably (d) butyl acrylate unit. According to this configuration, the expandable resin particles have the following advantages: (i) it is possible to provide expandable particles with suppressed adhesion and (ii) it is possible to provide an expandable molded article with excellent weldability.

[0047] The base resin of the present expandable resin particles may contain a structural unit derived from a crosslinking agent (hereinafter also referred to as a crosslinking agent unit). When the base resin of the present expandable resin particles contains a crosslinking agent unit, the expandable resin particles have the advantages of being able to provide expandable particles with excellent shrinkage suppression and excellent expandability.

[0048] The base resin of the present foamable resin particles may also contain a structural unit derived from an aromatic monomer (hereinafter also referred to as an aromatic unit) as a structural unit. As aromatic monomers, aromatic vinyl compounds such as styrene, α-methylstyrene, p-methylstyrene, tert-butylstyrene and chlorostyrene may be cited. When the base resin of the present foamable resin particles contains an aromatic unit, a foamed molded body with excellent strength can be obtained.

[0049] On the other hand, from the viewpoint of obtaining a foamed molded body with little residue during combustion, the amount of structural units derived from aromatic monomers (e.g., monomers having aromatic rings) and structural units having ring structures (e.g., structural units derived from alicyclic compounds, hereinafter also referred to as ring structural units) contained in the base resin of the foamable resin particles is preferably as small as possible. For example, the total amount of aromatic units and ring structural units contained in the base resin of the foamable resin particles is 2.5% by weight or less in 100% by weight of the base resin, preferably less than 2.5% by weight, more preferably less than 2.0% by weight, more preferably less than 1.5% by weight, further preferably less than 1.0% by weight, further preferably less than 0.5% by weight, and particularly preferably 0% by weight. That is, the base resin of the present foamable resin particles is particularly preferably free of aromatic units and ring structural units. Here, the “total amount of aromatic units and ring structure units contained in the substrate resin” means: (a) when the substrate resin contains aromatic units but does not contain ring structure units, it means the amount of aromatic units; (b) when the substrate resin contains ring structure units but does not contain aromatic units, it means the amount of ring structure units; (c) when the substrate resin contains aromatic units and ring structure units, it means the total amount of aromatic units and ring structure units.

[0050] (2-2. Foaming agent)

[0051] The foaming agent contained in the expandable resin particles is not particularly limited.

[0052] Specific examples of the aforementioned foaming agent include: (a) aliphatic hydrocarbons having 3 to 5 carbon atoms, such as propane, n-butane, isobutane, n-pentane, isopentane and neopentane; and (b) volatile foaming agents such as fluorocarbon compounds with zero ozone depletion coefficient, such as difluoroethane and tetrafluoroethane.

[0053] These foaming agents may be used alone or in combination of two or more.

[0054] In the present expandable resin particles, the content of the foaming agent is preferably 5 to 12 parts by weight, more preferably 7 to 10 parts by weight, relative to 100 parts by weight of the base resin. According to this configuration, there is an advantage that expandable resin particles having sufficient expandability can be provided without requiring heavy polymerization equipment.

[0055] (2-3. Other additives)

[0056] The foamable resin particles may contain other additives on the basis of the base resin and the foaming agent. Examples of the other additives include solvents, plasticizers, bubble regulators, flame retardants, flame retardant aids, heat radiation inhibitors, pigments, dyes, and antistatic agents.

[0057] The solvent is not particularly limited, but preferably has a boiling point of 50° C. or higher. Examples of the solvent having a boiling point of 50° C. or higher include: (a) aliphatic hydrocarbons having 6 or more carbon atoms (C6 or higher), such as toluene, hexane, and heptane; and (b) alicyclic hydrocarbons having C6 or higher, such as cyclohexane and cyclooctane.

[0058] From the viewpoint of obtaining foamable resin particles with excellent foamability, toluene and / or cyclohexane are preferably used as the solvent having a boiling point of 50°C or above. In the present foamable resin particles, the content of the solvent is preferably 1.5 to 3.0 parts by weight relative to 100 parts by weight of the base resin. When the content of the solvent relative to 100 parts by weight of the base resin is (a) 1.5 parts by weight or more, foamable resin particles with sufficient foaming power can be obtained, and when it is (b) 3.0 parts by weight or less, a foamed molded body with suppressed surface expansion, i.e., excellent dimensional stability, can be obtained.

[0059] The plasticizer is not particularly limited, but a high boiling point plasticizer having a boiling point of 200° C. or higher is preferred.

[0060] Examples of the high boiling point plasticizer include: (a) fatty acid glycerides such as stearic acid triglyceride, palmitic acid triglyceride, lauric acid triglyceride, stearic acid diglyceride, and stearic acid monoglyceride; (b) vegetable oils such as coconut oil, palm oil, and palm kernel oil; (c) aliphatic esters such as dioctyl adipate and dibutyl sebacate; and (d) organic hydrocarbons such as liquid paraffin and cyclohexane.

[0061] (2-4. Magnesium stearate)

[0062] The expandable methyl methacrylate resin particles according to one embodiment of the present invention contain 0.03 parts by weight or more and 0.14 parts by weight or less of magnesium stearate based on 100 parts by weight of the expandable methyl methacrylate resin particle body on the surface of the expandable methyl methacrylate resin particles.

[0063] By containing magnesium stearate as a fatty acid metal salt on the surface of the expandable resin particles, there is an advantage that the expandable resin particles and / or the mutual adhesion of the expandable resin particles to each other (sometimes referred to as "blocking" in this specification) during the production process of the expandable particles can be suppressed. In addition, by containing magnesium stearate on the surface of the expandable methyl methacrylate resin particles, the expandable methyl methacrylate resin particles have the following advantages: (i) it is possible to provide expandable particles with suppressed blocking and (ii) it is possible to provide a foamed molded product with excellent weldability.

[0064] In the present specification, “(X component) is contained on the surface of the expandable methacrylic resin particles” means “the surface of the expandable methacrylic resin particles is covered with (X component)”. In addition, in the present specification, “(X component) is contained on the surface of the expandable methacrylic resin particles” may also be referred to as “(X component) is coated on the surface of the expandable methacrylic resin particles”.

[0065] In addition, in the present specification, containing (X component) on the surface of the foamable resin particles refers to any one of the following states: (i) a state in which the entire amount of (X component) contained in the foamable resin particles forms a layer on the surface of the foamable resin particle body, (ii) a state in which the entire amount of (X component) contained in the foamable resin particles is impregnated in the surface layer portion of the foamable resin particle body, or (iii) a state in which a portion of (X component) contained in the foamable resin particles forms a layer on the surface of the foamable resin particle body and the remaining portion of the (X component) is impregnated in the surface layer portion of the foamable resin particle body.

[0066] As a mode of containing (X component) on the surface of the foamable resin particles, among the above-mentioned states (i) to (iii), it is more preferable that (i) the state in which the total amount of (X component) contained in the foamable resin particles forms a layer on the surface of the foamable resin particle body. According to this configuration, the foamable methyl methacrylate resin particles have the following advantages: (i) it is possible to provide foamable particles with suppressed blocking and (ii) it is possible to provide a foamed molded product with excellent weldability.

[0067] The content of magnesium stearate on the surface of the foamable resin particles is 0.03 parts by weight or more and 0.14 parts by weight or less, preferably 0.03 parts by weight or more and 0.12 parts by weight or less, more preferably 0.03 parts by weight or more and 0.10 parts by weight or less, more preferably 0.03 parts by weight or more and 0.08 parts by weight or less, further preferably 0.04 parts by weight or more and 0.06 parts by weight or less, and particularly preferably 0.04 parts by weight or more and 0.05 parts by weight or less, relative to 100 parts by weight of the base resin. According to this configuration, the foamable resin particles have the following advantages: (i) it is possible to provide foamable particles with suppressed adhesion and (ii) it is possible to provide a foamed molded article with excellent weldability.

[0068] It should be noted that the above value refers to the value obtained by rounding off the third decimal place with respect to the content of magnesium stearate relative to 100 parts by weight of the base resin. That is, for example, "0.03 parts by weight or more and 0.14 parts by weight or less relative to 100 parts by weight of the base resin" strictly means "0.025 parts by weight or more and less than 0.145 parts by weight relative to 100 parts by weight of the base resin".

[0069] (2-5. Welding accelerator)

[0070] The foamable resin particles preferably contain 0.10 parts by weight or less of a welding accelerator relative to 100 parts by weight of the foamable methyl methacrylate resin particle body on the surface of the foamable resin particles. According to this configuration, even when magnesium stearate is contained on the surface of the foamable resin particles, the obtained foamed molded article has an advantage of excellent welding properties.

[0071] As the welding accelerator, fatty acid triglycerides such as (a) lauric acid triglyceride, stearic acid triglyceride, linoleic acid triglyceride, hydroxystearic acid triglyceride, (b) lauric acid diglyceride, stearic acid diglyceride, linoleic acid diglyceride, fatty acid diglyceride such as (c) lauric acid monoglyceride, stearic acid monoglyceride, linoleic acid monoglyceride and (d) vegetable oils such as hydrogenated castor oil can be listed. These welding accelerators can be used alone or in combination. From the viewpoint of the affinity with the methyl methacrylate unit contained in the substrate resin and the excellent welding promotion effect, as the welding accelerator, preferably hydrogenated castor oil and stearic acid triglyceride, particularly preferably hydrogenated castor oil.

[0072] It should be noted that, when the above-mentioned substance is impregnated in (inside) the foamable resin particles, the above-mentioned substance is not considered as a welding accelerator. For example, when the above-mentioned substance is used during the manufacture of the foamable resin particle body (for example, from the beginning of the copolymerization step described later to the end of the foaming agent impregnation step), the above-mentioned substance used can be impregnated in (inside) the foamable resin particles. Therefore, the substance used during the manufacture of the foamable resin particle body is not considered as a welding accelerator.

[0073] The content of the welding accelerator on the surface of the foamable resin particles is preferably 0.01 parts by weight or more and 0.10 parts by weight or less, more preferably 0.02 parts by weight or more and 0.08 parts by weight or less, further preferably 0.03 parts by weight or more and 0.06 parts by weight or less, and particularly preferably 0.04 parts by weight or more and 0.05 parts by weight or less, relative to 100 parts by weight of the base resin. According to this constitution, the obtained foamable resin particles have the following advantages: (i) foamable particles with suppressed adhesion can be provided and (ii) a foamed molded article with excellent welding properties can be provided.

[0074] (2-6. Physical properties of expandable methyl methacrylate resin particles)

[0075] (Volume average particle size)

[0076] The volume average particle size of the present foamable resin particles is preferably 0.30 mm to 0.70 mm, more preferably 0.35 mm to 0.65 mm, further preferably 0.40 mm to 0.60 mm, and particularly preferably 0.45 mm to 0.55 mm. When the volume average particle size of the foamable resin particles is 0.30 mm or more, there is a tendency that the decrease in the foamability of the foamable resin particles during foaming is reduced and / or the increase in the amount of adhesion during foaming is reduced. When the volume average particle size of the foamable resin particles is 0.70 mm or less, for the foamable particles obtained by foaming the foamable resin particles, when the foamable particles are filled into the molding machine, the filling property of the narrow space becomes poor. It should be noted that the narrow space in the molding machine corresponds to the thin thickness of the obtained foamed molded body. The evaluation method of the volume average particle size of the foamable resin particles is described in detail in the following examples.

[0077] The volume average particle size of the expandable resin particles can be adjusted by changing (a) the amount of the initial dispersant (e.g., tricalcium phosphate, sodium α-olefin sulfonate), (b) the amount of the dispersant (e.g., tricalcium phosphate) added during the polymerization, and (c) the timing of adding the dispersant during the polymerization (e.g., the time from the initiation of polymerization to the addition of the dispersant).

[0078] [3. Method for producing expandable methyl methacrylate resin particles]

[0079] The method for producing the expandable resin particles is not particularly limited, and examples thereof include suspension polymerization in which a monomer mixture is polymerized in an aqueous suspension.

[0080] The method for producing expandable methyl methacrylate resin particles according to one embodiment of the present invention may include: a copolymerization step of copolymerizing a monomer mixture containing methyl methacrylate monomers and acrylate monomers; a blowing agent impregnation step of impregnating the obtained copolymer with a blowing agent; and a coating step of coating the surface of the obtained expandable methyl methacrylate resin particle body with 0.03 to 0.14 parts by weight of magnesium stearate relative to 100 parts by weight of the expandable methyl methacrylate resin particle body. The above-mentioned copolymerization step preferably also includes: (a) an initiation step of initiating the copolymerization of the monomer mixture in the presence of 0.20 to 1.20 parts by weight of a first water-slightly soluble inorganic salt relative to 100 parts by weight of the above-mentioned monomer mixture; and (b) an addition step of adding 0.08 to 0.50 parts by weight of a second water-slightly soluble inorganic salt relative to 100 parts by weight of the above-mentioned monomer mixture to the reaction mixture after the above-mentioned initiation step at a time when the polymerization conversion rate is 35% to 70%. In the copolymerization step, the methyl methacrylate monomer is preferably used in an amount of 93.0 to 99.0 parts by weight and the acrylate monomer is preferably used in an amount of 1.0 to 7.0 parts by weight based on 100 parts by weight of the total amount of the methyl methacrylate monomer and the acrylate monomer.

[0081] In the present specification, the "poorly water-soluble inorganic salt" refers to an inorganic salt having a solubility in water at 25°C of 0.1 mg / ml or less.

[0082] Hereinafter, “the method for producing expandable methyl methacrylate resin particles according to one embodiment of the present invention” may also be referred to as “the present production method”.

[0083] Since the present manufacturing method has the aforementioned structure, the obtained foamable resin particles have the following advantages: (i) it can provide foamable particles with suppressed adhesion and (ii) it can provide foamed molded products with excellent weldability. Since the present manufacturing method has the aforementioned structure, it can provide, for example, foamable methyl methacrylate resin particles of one embodiment of the present invention described in [2. Foamable methyl methacrylate resin particles]. The present manufacturing method is suitable for manufacturing the present foamable resin particles described in [2. Foamable methyl methacrylate resin particles]. It should be noted that the "copolymer" in the present manufacturing method is equivalent to the "base resin" contained in the foamable resin particles described in [2. Foamable methyl methacrylate resin particles].

[0084] Hereinafter, each step involved in the present production method will be described, and the description of the item [2. Expandable methyl methacrylate resin particles] will be appropriately cited except for the items described in detail below. In addition, the present expandable resin particles described in the item [2. Expandable methyl methacrylate resin particles] are preferably produced by the present production method, but may also be produced by a method other than the present production method. That is, the production method of the present expandable resin particles is not limited to the method of the present production method described below.

[0085] (3-1. Copolymerization step)

[0086] The copolymerization step in the present production method may be suspension polymerization in which a monomer mixture is polymerized in an aqueous suspension. Hereinafter, the copolymer (base resin) obtained in the copolymerization step may be simply referred to as "resin particles".

[0087] The "aqueous suspension" in the present invention refers to a liquid in which monomer droplets and / or resin particles are dispersed in water or an aqueous solution by stirring, etc. In the aqueous suspension, (a) a water-soluble surfactant and a monomer can be dissolved, and (b) a water-insoluble dispersant, a polymerization initiator, a chain transfer agent, a crosslinking agent, a bubble regulator, a flame retardant, a solvent, a plasticizer, etc. can be dispersed together with the monomer.

[0088] The weight ratio of the monomer and polymer (resin) to water or aqueous solution in the aqueous suspension is preferably 1.0 / 0.6 to 1.0 / 3.0, based on the ratio of the obtained methyl methacrylate resin to water or aqueous solution. It should be noted that the "aqueous solution" mentioned here refers to a solution formed by water and components other than the methyl methacrylate resin.

[0089] The copolymerization step includes an initiation step of initiating copolymerization of the monomer mixture in the presence of 0.20 to 1.20 parts by weight of the first sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture. The initiation step is a step of initiating copolymerization of the monomer mixture using, for example, an aqueous suspension containing (a) water, (b) a monomer mixture containing methyl methacrylate monomers and acrylate monomers, (c) 0.20 to 1.20 parts by weight of the first sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture, (d) a crosslinking agent, and optionally (e) a dispersant other than a polymerization initiator, a surfactant, and a sparingly water-soluble inorganic salt, a chain transfer agent, a bubble regulator, a flame retardant, a solvent, and a plasticizer.

[0090] In this specification, “before initiation of polymerization reaction” may be referred to as “initial polymerization stage.” The first poorly water-soluble inorganic salt and the optionally added polymerization initiator and the like mixed (added) into the aqueous suspension in the initiation step can be regarded as substances (raw materials) used in the initial polymerization stage.

[0091] In the initiation step, the first sparingly water-soluble inorganic salt can function as a dispersant. Examples of the first sparingly water-soluble inorganic salt used in the initiation step, i.e., the initial stage of polymerization, include tricalcium phosphate, magnesium pyrophosphate, hydroxyapatite, kaolin, and the like.

[0092] In the initiation step, (a) a water-soluble polymer such as polyvinyl alcohol, methylcellulose, polyacrylamide, polyvinyl pyrrolidone, and / or (b) an anionic surfactant such as sodium α-olefin sulfonate, sodium dodecylbenzene sulfonate, etc. may be used in combination with the first poorly water-soluble inorganic salt.

[0093] From the viewpoint of the ability to protect the resin particles and / or the monomer droplets, the first water-slightly soluble inorganic salt used in the initiation step is preferably tricalcium phosphate. From the viewpoint of the dispersion stability of the droplets, the initiation step is preferably a step of initiating copolymerization of the monomer mixture in the presence of tricalcium phosphate as the water-slightly soluble inorganic salt and sodium α-olefin sulfonate as the anionic surfactant.

[0094] The initiation step is preferably a step of initiating copolymerization of the monomer mixture in the presence of a first water-slightly soluble inorganic salt, preferably 0.20 to 1.20 parts by weight, more preferably 0.20 to 1.10 parts by weight, and further preferably 0.40 to 1.10 parts by weight, relative to 100 parts by weight of the monomer mixture. When initiating copolymerization of the monomer mixture in the presence of 0.20 parts by weight or more of the first water-slightly soluble inorganic salt relative to 100 parts by weight of the monomer mixture, there is no concern that the volume average particle size of the obtained foamable resin particles will become too large. When initiating copolymerization of the monomer mixture in the presence of 1.10 parts by weight or less of the first water-slightly soluble inorganic salt relative to 100 parts by weight of the monomer mixture, there is no concern that a large amount of microparticles of the foamable resin particles will be generated. That is, by initiating copolymerization of the monomer mixture in the presence of the first water-slightly soluble inorganic salt in an amount within the above range, foamable resin particles having a desired volume average particle size can be obtained with good yield.

[0095] In the initiation process, when a water-soluble polymer and / or anionic surfactant is used in combination with the first sparingly water-soluble inorganic salt, the concentration of the water-soluble polymer and / or anionic surfactant in the aqueous suspension is preferably 30 ppm to 100 ppm based on the concentration of the monomer mixture.

[0096] The copolymerization step includes, after the initiation step, adding 0.08 to 0.50 parts by weight of the second poorly water-soluble inorganic salt to the reaction mixture at a polymerization conversion rate of 35% to 70% based on 100 parts by weight of the monomer mixture.

[0097] In this specification, “after the initiation of the polymerization reaction” may be referred to as “during the polymerization.” In the adding step, the second poorly water-soluble inorganic salt added to the reaction mixture can be said to be a substance (raw material) used during the polymerization.

[0098] When the polymerization (copolymerization) of the monomer mixture in the copolymerization step is performed by suspension polymerization, the reaction mixture in the adding step may also be referred to as an aqueous suspension.

[0099] In the addition process, the second water-slightly soluble inorganic salt can function as a dispersant. As the second water-slightly soluble inorganic salt used in the addition process, i.e., during the polymerization, the substances already exemplified as the first water-slightly soluble inorganic salt can be cited. As the second water-slightly soluble inorganic salt, it is preferably one or more selected from the group consisting of tricalcium phosphate, hydroxyapatite and kaolin, and more preferably tricalcium phosphate. According to this configuration, there is the following advantage: it is possible to prevent the aggregation of the resin particles after the addition (addition) of the dispersant, thereby obtaining resin particles of the target particle size.

[0100] The adding step is preferably a step of adding the second water-slightly soluble inorganic salt to the reaction mixture at a polymerization conversion rate of 35% to 70% after the initiation step, preferably 0.08 to 0.50 parts by weight, more preferably 0.10 to 0.50 parts by weight, more preferably 0.10 to 0.40 parts by weight, further preferably 0.10 to 0.30 parts by weight, and particularly preferably 0.10 to 0.20 parts by weight, relative to 100 parts by weight of the monomer mixture. In the adding step, when 0.08 parts by weight or more of the second water-slightly soluble inorganic salt is added to the reaction mixture relative to 100 parts by weight of the monomer mixture, there is no concern that the volume average particle size of the obtained foamable resin particles will become too large. In the adding step, when 0.50 parts by weight or less of the second water-slightly soluble inorganic salt is added to the reaction mixture relative to 100 parts by weight of the monomer mixture, there is no concern that the production cost will increase due to excessive use of the water-slightly soluble inorganic salt. That is, in the adding step, by adding the second poorly water-soluble inorganic salt in an amount within the above range to the reaction mixture, expandable resin particles having a desired volume average particle size can be obtained at a low production cost.

[0101] The second sparingly water-soluble inorganic salt is preferably added to the reaction mixture at a time when the polymerization conversion rate is 35% to 70%, more preferably at a time when the polymerization conversion rate is 40% to 50%. According to this configuration, expandable resin particles having a desired volume average particle size can be obtained. The method for measuring the polymerization conversion rate in this specification is described in detail in the following examples.

[0102] In the copolymerization process, a crosslinking agent is preferably used. As a crosslinking agent, for example, a compound having two or more functional groups showing free radical reactivity can be cited. Among the compounds having two or more functional groups showing free radical reactivity, a difunctional monomer having two functional groups is preferably used as a crosslinking agent. In other words, the base resin of the present foamable resin particles preferably contains a difunctional monomer unit as a structural unit derived from a difunctional monomer as a crosslinking agent unit. According to this structure, there are the following advantages: (a) the foamability of the foamable resin particles is more excellent, (b) the shrinkage inhibition of the foamed particles formed by foaming the foamable resin particles is more excellent, and (c) the foamable resin particles (i) can provide foamed particles with suppressed adhesion, and (ii) can provide a foamed molded body with excellent weldability.

[0103] Examples of the bifunctional monomer include: (a) compounds obtained by esterifying both terminal hydroxyl groups of ethylene glycol with (meth)acrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, and triethylene glycol di(meth)acrylate, and / or compounds obtained by esterifying both terminal hydroxyl groups of the ethylene glycol oligomer with (meth)acrylic acid, (b) compounds obtained by esterifying the hydroxyl groups of diols with acrylic acid or methacrylic acid, such as neopentyl glycol di(meth)acrylate, hexanediol di(meth)acrylate (e.g., 1,6-hexanediol diacrylate, etc.), and butanediol di(meth)acrylate, and (c) aromatic compounds having two alkenyl groups, such as divinylbenzene, etc. Hexanediol di(meth)acrylate is easy to adjust the molecular weight of the base resin, and therefore, as the bifunctional monomer, hexanediol di(meth)acrylate such as 1,6-hexanediol diacrylate is preferred. In the present specification, “(meth)acrylate” means methacrylate and / or acrylate, and “(meth)acrylic acid” means methacrylic acid and / or acrylic acid.

[0104] In the copolymerization step, the amount of the crosslinking agent used is preferably 0 part by weight or more and less than 0.20 part by weight, more preferably 0 to 0.19 part by weight, more preferably 0 to 0.17 part by weight or less, more preferably 0 to 0.15 part by weight or less, and further preferably 0 to 0.13 part by weight, relative to 100 parts by weight of the total amount of the methyl methacrylate monomer and the aforementioned acrylate monomer. According to the above-mentioned structure, there are the following advantages: (a) the foaming property of the foamable resin particles is excellent, (b) the shrinkage inhibition property of the foamable particles formed by foaming the foamable resin particles is excellent, and the foamable resin particles (i) can provide foamed particles with suppressed adhesion, and (ii) can provide a foamed molded product with excellent weldability. In the copolymerization step, the amount of the crosslinking agent used can be 0.01 part by weight or more, 0.03 part by weight or more, 0.05 part by weight or more, or 0.08 part by weight or more, relative to 100 parts by weight of the total amount of the methyl methacrylate monomer and the aforementioned acrylate monomer.

[0105] In the present expandable resin particles, a crosslinking agent is incorporated into the resulting copolymer (base resin). Therefore, the base resin of the present expandable resin particles may include a structural unit derived from a crosslinking agent. On the other hand, the amount of the crosslinking agent used is a trace amount relative to the amount of the monomer mixture, so the amount of the crosslinking agent used (in other words, the content of the structural unit derived from the crosslinking agent) is not considered when calculating the amount (content) of the base resin. Therefore, in this specification, the amount of the monomer mixture used does not include the amount of the difunctional monomer.

[0106] The copolymerization step is preferably implemented in at least two stages by changing the polymerization temperature. For convenience, the following two polymerization steps with different polymerization temperatures are referred to as the first polymerization step and the second polymerization step. It can also be said that the copolymerization step preferably includes a continuous first polymerization step and a second polymerization step with different polymerization temperatures.

[0107] The copolymerization step preferably includes, for example: (a) a first polymerization step carried out at a polymerization temperature of 70° C. to 90° C. and using a low-temperature decomposition type polymerization initiator, and (b) a second polymerization step carried out continuously with the first polymerization step and carried out at a polymerization temperature higher than that of the first polymerization step (e.g., 90° C. to 110° C.) and using a high-temperature decomposition type polymerization initiator. In the copolymerization step, it is preferred that the main polymerization reaction is carried out in the first polymerization step, and the residual monomer is reduced in the second polymerization step.

[0108] As the polymerization initiator, a free radical generating polymerization initiator commonly used for manufacturing thermoplastic polymers can be used. Representative free radical generating polymerization initiators include: (a) organic peroxides such as benzoyl peroxide, lauroyl peroxide, tert-butyl peroxybenzoate, isopropyl tert-butyl peroxycarbonate, butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxyisopropyl carbonate, di-tert-butyl peroxyhexahydroterephthalate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, and tert-butylperoxy-2-ethylhexyl monocarbonate, and (b) azo compounds such as azobisisobutyronitrile and azobisdimethylvaleronitrile. These polymerization initiators may be used alone or in combination of two or more.

[0109] Among the above-mentioned free radical generating polymerization initiators, (a) benzoyl peroxide, lauroyl peroxide, tert-butyl peroxypivalate, di-tert-butyl peroxyhexahydroterephthalate, azobisisobutyronitrile and azobisdimethylvaleronitrile are low temperature decomposition type polymerization initiators, and (b) tert-butyl peroxybenzoate, isopropyl tert-butyl peroxycarbonate, butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisopropyl carbonate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane and tert-butylperoxy-2-ethylhexyl monocarbonate are high temperature decomposition type polymerization initiators.

[0110] The amount of the polymerization initiator used is preferably 0.05 to 0.5 parts by weight based on 100 parts by weight of the monomer mixture, the total amount used in the first polymerization step and the amount used in the second polymerization step. According to this configuration, expandable resin particles having excellent expandability can be obtained.

[0111] The initiation step may be (a) a step of initiating copolymerization of the monomer mixture in the presence of a first sparingly water-soluble inorganic salt, a low-temperature decomposition type polymerization initiator, and a high-temperature decomposition type polymerization initiator, or (b) a step of initiating copolymerization of the monomer mixture in the presence of a first sparingly water-soluble inorganic salt and a low-temperature decomposition type polymerization initiator. When the initiation step is a step of initiating copolymerization of the monomer mixture in the presence of a first sparingly water-soluble inorganic salt and a low-temperature decomposition type polymerization initiator, the high-temperature decomposition type polymerization initiator may be added to the reaction mixture (aqueous suspension) after the initiation step, i.e., during the polymerization.

[0112] In the present expandable resin particles, a part of the polymerization initiator is sometimes incorporated into the obtained copolymer. Therefore, the base resin of the present expandable resin particles may contain a polymerization initiator. On the other hand, the amount of the polymerization initiator used is a trace amount relative to the amount of the monomer mixture, so the amount of the polymerization initiator used is not considered when calculating the amount (content) of the base resin.

[0113] In the copolymerization process, a chain transfer agent is preferably used. As a chain transfer agent, there is no particular limitation, and known substances used in the polymerization of methyl methacrylate resins can be used. As a chain transfer agent, for example, monofunctional chain transfer agents such as (a) alkyl mercaptans and thioglycolates and (b) polyfunctional chain transfer agents formed by esterifying polyol hydroxyl groups with thioglycolic acid or 3-mercaptopropionic acid such as ethylene glycol, neopentyl glycol, trimethylolpropane, sorbitol, etc. As alkyl mercaptans, n-octyl mercaptan, n-dodecyl mercaptan and tert-dodecyl mercaptan can be listed. The amount of the chain transfer agent used is, for example, preferably 0.100 parts by weight or more and less than 0.500 parts by weight, more preferably 0.200 parts by weight or more and less than 0.300 parts by weight relative to 100 parts by weight of the substrate resin.

[0114] In the present expandable resin particles, a part of the chain transfer agent is sometimes incorporated into the obtained copolymer. Therefore, the base resin of the present expandable resin particles may contain a chain transfer agent. On the other hand, the amount of the chain transfer agent used is a trace amount relative to the amount of the monomer mixture, so the amount of the chain transfer agent used is not considered when calculating the amount (content) of the base resin.

[0115] In the copolymer, a light stabilizer is preferably used. As the light stabilizer, there is no particular limitation as long as it is a commonly known light stabilizer. As the light stabilizer, commercial products such as Sumisorb 200 (registered trademark) (manufactured by Sumika Chemtex Company, Ltd.) can also be used. The amount of the light stabilizer used is preferably 0.01 to 0.05 parts by weight relative to 100 parts by weight of the monomer component contained in the monomer mixture.

[0116] (3-2. Foaming agent impregnation step)

[0117] In the blowing agent impregnation step, the methyl methacrylate resin particles as the copolymer obtained in the copolymerization step are impregnated with the blowing agent, thereby obtaining an expandable methyl methacrylate resin particle body.

[0118] The blowing agent impregnation step may be performed at any time, and may be performed together with the second polymerization step, or may be performed after the second polymerization step.

[0119] The foaming agent impregnation process preferably impregnates the obtained copolymer with the foaming agent at a time when the polymerization conversion rate from the monomer to the copolymer is 80% to 95%. When the foaming agent is impregnated into the copolymer at a time when the polymerization conversion rate is 80% or more, the foaming agent is moderately impregnated into the interior of the copolymer, so there is no concern about the aggregation of the copolymers due to the softening of the copolymer, and the manufacturing yield becomes good. When the foaming agent is impregnated into the copolymer at a time when the polymerization conversion rate is 95% or less, the foaming agent is fully impregnated into the interior of the copolymer, so there is no concern about the formation of a double bubble structure (hard core) in the foamed particles formed by foaming the obtained foamable resin particles. As a result, by in-mold molding of the foamed particles, a foamed molded body with excellent surface aesthetics can be obtained.

[0120] In the blowing agent impregnation step, the amount of the blowing agent impregnated into the methyl methacrylate resin particles as the copolymer is the same as the content of the blowing agent in the expandable resin particles described in the item (2-2. Blowing agent) of [2. Expandable methyl methacrylate resin particles], including a preferred embodiment. According to this configuration, expandable resin particles having sufficient expandability can be obtained, and aggregation of the copolymer is not caused in the blowing agent impregnation step, so that the expandable resin particles can be safely produced.

[0121] In the blowing agent impregnation step, the treatment temperature (also referred to as impregnation temperature) and the treatment time (also referred to as impregnation time) when impregnating the copolymer with the blowing agent are not particularly limited.

[0122] In the blowing agent impregnation process, the impregnation temperature when the blowing agent is impregnated into the copolymer is preferably below 95°C to 120°C, and more preferably below 100°C to 117°C. When the impregnation temperature is above 95°C, the blowing agent is fully impregnated into the interior of the copolymer, so there is no concern about forming a double bubble structure (hard core) in the foamed particles obtained by foaming the obtained foamable resin particles. As a result, by in-mold molding the foamed particles, a foamed molded body with excellent surface aesthetics can be obtained. When the impregnation temperature is below 120°C, the pressure in the polymerization machine will not become too high, so foamable resin particles that can provide foamed particles with a uniform bubble structure can be obtained without the need for heavy-duty impregnation equipment that can withstand high pressures.

[0123] In the present production method, when a solvent (for example, a solvent having a boiling point of 50° C. or higher) is used, the solvent is preferably added to the reaction mixture (aqueous suspension) immediately before or simultaneously with the blowing agent impregnation step.

[0124] (3-3. Coating step)

[0125] In the coating step, the surface of the expandable methyl methacrylate resin particle body obtained in the blowing agent impregnation step is coated with 0.03 parts by weight or more and 0.14 parts by weight of magnesium stearate based on 100 parts by weight of the expandable methyl methacrylate resin particle body. By going through the coating step, expandable resin particles can be obtained.

[0126] It is preferred that the foamable resin particle body or the foamable resin particles are further coated with a welding accelerator before (a), at the same time as (b), or after (c) the magnesium stearate is applied to the surface of the foamable resin particle body. That is, the coating step is preferably any of the following steps: (i) a step of coating the surface of the foamable resin particle body obtained in the copolymerization step and the foaming agent impregnation step with a welding accelerator and then coating magnesium stearate, (ii) a step of simultaneously coating magnesium stearate and a welding accelerator, or (iii) a step of coating the foamable resin particles obtained after magnesium stearate is applied and then coating the welding accelerator.

[0127] In addition, about the welding accelerator, since it is the same as what was described in the said item (2-5. welding accelerator), that description is quoted and the description is abbreviate|omitted here.

[0128] The fatty acid metal salt, the welding accelerator, and the like applied to the surface of the expandable resin particle body are sometimes referred to as “external additives.” Examples of the external additives include antistatic agents.

[0129] [4. Methyl methacrylate resin foam particles]

[0130] The methyl methacrylate resin foamed particles according to one embodiment of the present invention are foamed particles obtained by foaming the foamable methyl methacrylate resin particles described in [2. Foamable methyl methacrylate resin particles] or the foamable methyl methacrylate resin particles produced by the production method described in [3. Production method of foamable methyl methacrylate resin particles].

[0131] According to this configuration, the methyl methacrylate resin foamed beads according to one embodiment of the present invention have advantages in that foamed beads with suppressed blocking can be provided, and a foamed molded article having excellent weldability can be provided.

[0132] Hereinafter, “the methyl methacrylate resin foamed particles according to one embodiment of the present invention” may also be referred to as “the present foamed particles”.

[0133] The present expandable resin particles can be made into expandable particles by a common expansion method. Specifically, for example, the methyl methacrylate resin expandable particles can be obtained by sequentially performing the following operations (1) to (3): (1) adding expandable methyl methacrylate resin particles into a container equipped with a stirrer; (2) heating the expandable methyl methacrylate resin particles using a heat source such as steam; (3) expanding the expandable methyl methacrylate resin particles to a desired expansion ratio by the above-mentioned (2) to obtain methyl methacrylate resin expandable particles.

[0134] The foaming of the expandable methyl methacrylate resin particles can also be said to be foaming performed in advance in order to obtain the methyl methacrylate resin foamed molded product described later from the expandable methyl methacrylate resin particles. Therefore, the foaming of the expandable methyl methacrylate resin particles is sometimes also referred to as "pre-foaming", and the methyl methacrylate resin foamed particles are sometimes also referred to as "methyl methacrylate resin pre-foamed particles".

[0135] The method for evaluating the volume ratio of expanded beads will be described in detail in the examples below.

[0136] [5. Methyl methacrylate resin foamed product]

[0137] The methyl methacrylate resin foam molded article according to one embodiment of the present invention is a foam molded article obtained by in-mold molding the methyl methacrylate resin foamed particles described in the section [4. Methyl methacrylate resin foamed particles].

[0138] Hereinafter, the "methyl methacrylate-based resin foamed molded product according to one embodiment of the present invention" may also be referred to as the "present foamed molded product".

[0139] The foamed particles can be molded by a conventional in-mold molding method to form a foamed molded article. Specifically, for example, the methyl methacrylate resin foamed molded article can be obtained by sequentially performing the following operations (1) to (3): (1) filling a mold that can be closed but not airtight with methyl methacrylate resin foamed particles; (2) heating the methyl methacrylate resin foamed particles with water vapor; (3) fusing the methyl methacrylate resin foamed particles to each other by the above-mentioned (2), thereby obtaining a methyl methacrylate resin foamed molded article.

[0140] The methyl methacrylate resin foam molded product according to one embodiment of the present invention has an advantage of excellent weldability. For this reason, the methyl methacrylate resin foam molded product according to one embodiment of the present invention can be suitably used as a lost pattern.

[0141] [6. Lost foam]

[0142] The lost foam according to one embodiment of the present invention includes the methyl methacrylate resin foam molded article described in the section [5. Methyl methacrylate resin foam molded article].

[0143] Since the lost foam pattern according to one embodiment of the present invention includes a foamed molded article having excellent weldability, it can be suitably used for various metal castings.

[0144] One embodiment of the present invention may have the following structure.

[0145] [1] A foamable methyl methacrylate resin particle comprising: a base resin containing methyl methacrylate units and acrylate units as structural units; and a foaming agent;

[0146] The surface of the expandable methyl methacrylate resin particle contains 0.03 parts by weight or more and 0.14 parts by weight or less of magnesium stearate based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

[0147] [2] The expandable methyl methacrylate resin particles according to [1], wherein

[0148] The surface of the expandable methyl methacrylate resin particle contains 0.10 parts by weight or less of a fusion promoter based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

[0149] [3] The expandable methyl methacrylate resin particles according to [1] or [2], wherein the acrylic acid ester unit is a butyl acrylate unit.

[0150] [4] The expandable methyl methacrylate resin particles according to any one of [1] to [3], wherein the expandable methyl methacrylate resin particles have a volume average particle size of 0.30 mm to 0.70 mm.

[0151] [5] Methyl methacrylate resin foamed particles obtained by foaming the foamable methyl methacrylate resin particles according to any one of [1] to [4].

[0152] [6] A methyl methacrylate resin foamed molded product obtained by in-mold molding the methyl methacrylate resin foamed particles described in [5].

[0153] [7] A lost foam pattern comprising the methyl methacrylate resin foam molded product described in [6].

[0154] [8] A method for producing expandable methyl methacrylate resin particles, comprising:

[0155] A copolymerization step of copolymerizing a monomer mixture comprising methyl methacrylate monomers and acrylate monomers;

[0156] a blowing agent impregnation step of impregnating the obtained copolymer with a blowing agent; and

[0157] In the coating step, 0.03 parts by weight or more and 0.14 parts by weight or less of magnesium stearate is coated on the surface of the obtained expandable methyl methacrylate resin particle body based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

[0158] [9] The production method according to [8], wherein the copolymerization step further comprises:

[0159] (a) an initiation step of initiating copolymerization of the monomer mixture in the presence of 0.20 to 1.20 parts by weight of a first sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture; and

[0160] (b) an adding step of adding 0.08 to 0.50 parts by weight of a second sparingly water-soluble inorganic salt to the reaction mixture after the initiation step when the polymerization conversion rate reaches 35% to 70%.

[0161]

[10] A method for producing a methyl methacrylate resin foam molded product, comprising the step of in-mold molding the methyl methacrylate resin foamed particles described in [5].

[0162] Example

[0163] An embodiment of the present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited thereto.

[0164] (Volume Average Particle Diameter of Expandable Methyl Methacrylate Resin Particles)

[0165] The particle size of the expandable methyl methacrylate resin particles was measured on a volume basis at intervals of 0.005 mm in cut width using a Millitrac JPA particle size analyzer with image processing. The obtained results were expressed as cumulative distribution, and the particle size at which the volume accumulation reached 50% was defined as the volume average particle size.

[0166] (Evaluation of Adhesive Properties of Methyl Methacrylate Resin Foamed Particles)

[0167] Using expandable methyl methacrylate resin particles, the following (1) to (4) are sequentially performed to obtain expandable methyl methacrylate resin particles having a volume ratio of 50 times: (1) the expandable methyl methacrylate resin particles are spread in a square flat bottom pan (vat) to a thickness of 2 to 3 cm, and dried in a dryer at 60° C. for 5 days; (2) the expandable methyl methacrylate resin particles (850 g) obtained in the above (1) are introduced into a large open pressure foaming machine; BHP110 manufactured by Kogyo Co., Ltd.; (3) blowing water vapor into the foaming machine under the conditions of a steam blowing pressure of 0.10 MPa to 0.16 MPa and a pressure in the foaming machine of 0.30 MPa to 0.035 MPa to heat the foamable methyl methacrylate resin particles; (4) foaming the foamable methyl methacrylate resin particles through the above (3) until the volume ratio reaches 50 times, thereby obtaining methyl methacrylate resin foamed particles with a volume ratio of 50 times.

[0168] The expanded beads were sieved with a net having a mesh size of 5 mm, and the expanded beads remaining on the net were referred to as “stuck expanded beads.” The weight of the stuck expanded beads was measured, and the sticking amount (weight %) was calculated using the following calculation formula.

[0169] Blocking amount (weight %)=(weight of stuck expanded beads (g) / resin input amount (g))×100.

[0170] Based on the obtained blocking amount, the blocking property of the expanded beads was evaluated according to the following criteria.

[0171] A (very good): The amount of blocking (weight %) is 0.10 weight % or less

[0172] B (good): The amount of blocking (weight %) is more than 0.10 weight % and less than 0.20 weight %

[0173] C (poor): The blocking amount (weight %) exceeded 0.20 weight %.

[0174] (Weldability of Methyl Methacrylate Resin Foam Molded Article)

[0175] Using methyl methacrylate resin foam beads, the following (1) to (4) are sequentially performed to obtain a methyl methacrylate resin foam molded article: (1) the methyl methacrylate resin foam beads having a volume ratio of 50 times are allowed to stand at room temperature (25° C.) for 3 days; (2) a box-shaped mold (KR-57 manufactured by DAISEN) having a bottom thickness of 30 mm, a side thickness of 25 mm, and dimensions of 550 mm in length, 350 mm in width, and 120 mm in height is filled with methyl methacrylate at a volume ratio of 50 times. (3) blowing steam into the mold at a steam blowing pressure of 0.30 MPa to 0.50 MPa, and performing in-mold molding using steam heating under the condition that the pressure in the mold is 0.050 MPa to 0.80 MPa until the foaming pressure reaches 0.100 MPa to 0.180 MPa, so that the methyl methacrylate resin foam particles are welded to each other; (4) after the foaming pressure reaches 0.100 MPa to 0.180 MPa, the mold is left for 100 seconds, and then the foamed molded body is taken out.

[0176] The obtained thermoplastic resin foam was dried at room temperature for 24 hours, and then the following weldability evaluation was performed.

[0177] The obtained thermoplastic resin foam was fractured, and the fracture surface was visually observed. All particles constituting the fracture surface and foamed particles fractured outside the particle interface were measured, and the fusion rate (%) was calculated based on the following formula:

[0178] Welding rate (%) = number of particles fractured at other than the particle interface in the fracture surface / number of particles constituting the fracture surface×100.

[0179] Based on the obtained fusion rate, the fusion property of the foamed molded article was evaluated according to the following criteria.

[0180] A (very good): welding rate exceeds 70%

[0181] B (good): The welding rate is 60% or more and 70% or less

[0182] C (poor): The fusion rate is less than 60%.

[0183] (Volume ratio of methyl methacrylate resin foamed particles)

[0184] The volume ratio of the methyl methacrylate resin foamed particles was obtained by sequentially carrying out the following (1) to (3): (1) 10 g of the foamed particles were weighed and placed in a 1000 cm 3 (2) measuring the volume of 10 g of foamed particles according to the scale of the measuring cylinder; (3) calculating the volume ratio of the foamed particles by the following formula;

[0185] Volume ratio (cm 3 / g) = volume of foamed particles (cm 3 ) / 10g.

[0186] In this specification, the volume ratio of the foamed particles may also be referred to as the foaming ratio. In addition, the unit of the volume ratio is actually cm based on the above formula. 3 / g, but in this specification, for convenience, the unit of volume ratio is expressed as "times".

[0187] (Polymerization Conversion Rate of Expandable Methyl Methacrylate Resin Particles)

[0188] During the polymerization, the aqueous suspension was sampled and filtered. The weight of the resin component remaining on the filter paper was weighed, and the obtained weight was used as the weight before heating. Then, after adding a polymerization inhibitor to the resin component, the resin component was heated at 150°C for 30 minutes to remove the volatile components. Then, the weight of the obtained resin component was weighed, and the obtained weight was used as the weight after heating. The polymerization conversion rate was calculated using the following formula.

[0189] Polymerization conversion rate (%) = weight after heating / weight before heating×100.

[0190] (Example 1)

[0191] In a 6L autoclave equipped with a stirrer, 150 parts by weight of water, 0.46 parts by weight of tricalcium phosphate and 0.0075 parts by weight of sodium α-olefin sulfonate as the first sparingly water-soluble inorganic salt, 0.08 parts by weight of lauroyl peroxide and 0.1 parts by weight of 1,1-bis(tert-butylperoxy)cyclohexane as polymerization initiators, 0.1 parts by weight of 1,6-hexanediol diacrylate as a crosslinking agent, 0.240 parts by weight of n-dodecyl mercaptan as a chain transfer agent, and 0.03 parts by weight of "Sumisorb 200" (registered trademark, manufactured by Sumika Chemtex Company, Ltd.) as a light stabilizer were added to prepare a mixed solution containing the first sparingly water-soluble inorganic salt. Then, 97.5 parts by weight of methyl methacrylate and 2.5 parts by weight of butyl acrylate as a monomer mixture and 1.0 parts by weight of toluene as a solvent were added to the mixed solution to prepare an aqueous suspension. Next, the temperature of the aqueous suspension was raised to 80°C to initiate polymerization, i.e., the initiation step was performed. After 1 hour and 45 minutes from the initiation of polymerization (after the initiation step), the polymerization conversion rate was measured and the result was 40% to 50%. After 1 hour and 45 minutes from the initiation of polymerization (after the initiation step), 0.12 parts by weight of tricalcium phosphate as the second poorly water-soluble inorganic salt was added to the reaction mixture (aqueous suspension) to perform the addition step.

[0192] After another 2 hours and 35 minutes, 1.5 parts by weight of cyclohexane as a solvent and 9 parts by weight of normal rich butane (the weight ratio of normal butane to isobutane in normal rich butane (normal butane / isobutane) is 70 / 30) as a foaming agent are added to the aqueous suspension. Then, the temperature of the aqueous suspension is raised to 101°C. Next, the temperature of the aqueous suspension is maintained at 101°C for 10 hours, thereby performing copolymerization and impregnation of the foaming agent into the copolymer (copolymerization process and foaming agent impregnation process). Then, the aqueous suspension is cooled. After the aqueous suspension is cooled, the obtained product is washed, dehydrated and dried, thereby obtaining a foamable methyl methacrylate resin particle body.

[0193] The obtained expandable methyl methacrylate resin particle body was sieved with sieves having mesh sizes of 0.235 mm and 0.700 mm. By this operation, expandable methyl methacrylate resin particle bodies having a particle size of 0.235 mm to 0.700 mm were extracted. Then, 0.03 parts by weight of magnesium stearate as a fatty acid metal salt and 0.05 parts by weight of hydrogenated castor oil as a welding accelerator were applied to the surface of the expandable methyl methacrylate resin particle body based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

[0194] According to the above method, each evaluation item (the amount of blocking during pre-foaming of the expandable methyl methacrylate resin particles and the fusion rate of the methyl methacrylate resin foamed molded product) was evaluated.

[0195] (Example 2)

[0196] Except that the amount of magnesium stearate used was changed to 0.04 parts by weight, the same operation as in Example 1 was carried out to obtain expandable methyl methacrylate resin particles.

[0197] (Example 3)

[0198] Except that the amount of magnesium stearate used was changed to 0.05 parts by weight, the same operation as in Example 1 was carried out to obtain expandable methyl methacrylate resin particles.

[0199] (Example 4)

[0200] Except that the amount of magnesium stearate used was changed to 0.10 parts by weight, the same operation as in Example 1 was carried out to obtain expandable methyl methacrylate resin particles.

[0201] (Example 5)

[0202] Except that the amount of magnesium stearate used was changed to 0.13 parts by weight, the same operation as in Example 1 was carried out to obtain expandable methyl methacrylate resin particles.

[0203] (Comparative Example 1)

[0204] Except that the amount of magnesium stearate used was changed to 0.02 parts by weight, the same operation as in Example 1 was carried out to obtain expandable methyl methacrylate resin particles.

[0205] (Comparative Example 2)

[0206] Except that the amount of magnesium stearate used was changed to 0.15 parts by weight, the same operation as in Example 1 was carried out to obtain expandable methyl methacrylate resin particles.

[0207] (Comparative Example 3)

[0208] Except that the amount of magnesium stearate used was changed to 0.20 parts by weight, the same operation as in Example 1 was carried out to obtain expandable methyl methacrylate resin particles.

[0209] (Comparative Example 4)

[0210] The same operation as in Example 1 was carried out except that the fatty acid metal salt used was changed to 0.40 parts by weight of zinc stearate to obtain expandable methyl methacrylate resin particles.

[0211] (Comparative Example 5)

[0212] The same operation as in Example 1 was carried out except that the fatty acid metal salt used was changed to 0.50 parts by weight of zinc stearate to obtain expandable methyl methacrylate resin particles.

[0213] (Comparative Example 6)

[0214] The same operation as in Example 1 was carried out except that the fatty acid metal salt used was changed to 0.60 parts by weight of zinc stearate to obtain expandable methyl methacrylate resin particles.

[0215] [Table 1]

[0216]

[0217] [Table 2]

[0218]

[0219] (Summarize)

[0220] As can be seen from Examples 1 to 5, when a specific amount (0.03 to 0.13 parts by weight relative to 100 parts by weight of the main body of the foamable resin particles) of magnesium stearate is contained on the surface of the foamable resin particles, it is possible to provide foamable methyl methacrylate resin particles that satisfy the following (i) and (ii): (i) foamable particles with suppressed sticking can be provided, and (ii) a foamed molded article with excellent weldability can be provided.

[0221] In addition, the amount of magnesium stearate contained on the surface of the expandable resin particles increased in the order of Comparative Example 1, Examples 1, 2, 3, 4, and 5, but surprisingly, the best weldability of the foamed molded article was obtained in Examples 1 and 2. This result indicates that there is a range of magnesium stearate content in which the tackiness and weldability are positively correlated.

[0222] On the other hand, when zinc stearate was contained on the surface of the expandable resin particles, the blocking property and the fusion property were inversely related (negatively related) regardless of the content of zinc stearate (Comparative Examples 4 to 6).

[0223] That is, it is shown that the effects on the adhesiveness and the fusibility are greatly different between the case where magnesium stearate is contained on the surface of the expandable resin particles and the case where zinc stearate is contained on the surface of the expandable resin particles.

[0224] The effects described above are novel and qualitatively different effects discovered for the first time by the present inventors, and it can be said that these effects could not be predicted by those skilled in the art based on the technical level at the time of filing the application.

[0225] Industrial Applicability

[0226] According to one embodiment of the present invention, expandable methyl methacrylate resin particles that satisfy the following (i) and (ii) can be provided: (i) foamed particles with suppressed adhesion can be provided, and (ii) a foamed molded article with excellent weldability can be provided. Therefore, one embodiment of the present invention can be suitably used as a lost foam when metal casting is performed using a full mold casting method.

Claims

1. A foamable methyl methacrylate resin particle, comprising: a base resin containing methyl methacrylate units and acrylate units as structural units and a foaming agent, The surface of the expandable methyl methacrylate resin particles contains 0.03 parts by weight or more and 0.14 parts by weight or less of magnesium stearate based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

2. The expandable methyl methacrylate resin particles according to claim 1, wherein The surface of the expandable methyl methacrylate resin particle contains 0.10 parts by weight or less of a welding accelerator based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

3. The expandable methyl methacrylate resin particles according to claim 1, wherein The acrylate unit is a butyl acrylate unit.

4. The expandable methyl methacrylate resin particles according to claim 1, wherein The volume average particle size of the expandable methyl methacrylate resin particles is 0.30 mm to 0.70 mm. 5 . Methyl methacrylate resin foamed particles obtained by foaming the foamable methyl methacrylate resin particles according to claim 1 . 6 . A methyl methacrylate resin foamed molded product, which is obtained by in-mold molding the methyl methacrylate resin foamed particles according to claim 5 . 7 . A lost foam comprising the methyl methacrylate resin foamed molded article according to claim 6 .

8. A method for producing expandable methyl methacrylate resin particles, comprising: A copolymerization step of copolymerizing a monomer mixture comprising methyl methacrylate monomers and acrylate monomers; A blowing agent impregnation step of impregnating the obtained copolymer with a blowing agent; as well as In the coating step, 0.03 parts by weight or more and 0.14 parts by weight or less of magnesium stearate is coated on the surface of the obtained expandable methyl methacrylate resin particle body based on 100 parts by weight of the expandable methyl methacrylate resin particle body.

Citation Information

Patent Citations

  • Method for manufacturing foamable resin particle, foamable resin particle and foam-molded article

    JP2001270959A

  • Foamable acrylic resin particle, acrylic resin foam particle, and acrylic resin foam particle molding

    JP2020147736A

  • Foamable acrylic resin particles, acrylic resin foaming particles and acrylic resin foaming particle molds

    JP2021024885A